2020
DOI: 10.1038/s41598-020-64882-9
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin, at clinically achievable dose, protects mice and prevents recurrence from Clostridioides difficile infection

Abstract: Clostridioides difficile is the leading cause of nosocomial infections and a worldwide urgent public health threat. Without doubt, there is an urgent need for new effective anticlostridial agents due to the increasing incidence and severity of C. difficile infection (CDI). The aim of the present study is to investigate the in vivo efficacy of auranofin (rheumatoid arthritis FDA-approved drug) in a CDI mouse model and establish an adequate dosage for treatment. The effects of increased C. difficile inoculum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
5
19
0
Order By: Relevance
“…51 In Vivo Efficacy of HSGN-218 in a CDI Mouse Model. 52 The potent antibacterial activities of HSGN-218 against C. difficile prompted us to investigate its efficacy in a CDI mouse model and its potential to protect mice from CDI recurrence, as described before. As shown in Figure 4, vancomycin (10 mg/kg) protected 100% of mice up to five days, as previously reported.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…51 In Vivo Efficacy of HSGN-218 in a CDI Mouse Model. 52 The potent antibacterial activities of HSGN-218 against C. difficile prompted us to investigate its efficacy in a CDI mouse model and its potential to protect mice from CDI recurrence, as described before. As shown in Figure 4, vancomycin (10 mg/kg) protected 100% of mice up to five days, as previously reported.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…[2,3] Auranofin is an FDA-approved drug previously used as an anti-inflammatory aid in the treatment of rheumatoid arthritis (Figure 1). It has since been tested for other diseases, showing antibacterial, [4][5][6][7][8][9][10][11] antifungal, [12][13][14] antiparasitic, [15,16] antiviral, [17][18][19][20][21] and antitumor [22] activities. The main mode of action (MOA) of auranofin has been suggested to be the inhibition of thioredoxin reductase (TrxR).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that auranofin has a good safety profile [ 28 ]. Chronic exposure of patients to auranofin over extended periods of time was safe with no cumulative toxicity observed over five years [ 28 ].The usual adult dosage of auranofin is 6–9 mg daily for up to six months, which is a much longer course of treatment than what would be expected for auranofin as an antibacterial agent [ 20 , 49 ]. Consequently, the dose used in this study, (0.25 mg/kg), is within range of clinically-administered human doses.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, auranofin possesses antibacterial activity against Mycobacterium tuberculosis [ 26 ]. Auranofin also demonstrated antimicrobial activity against Gram-positive bacteria in different mouse models, including skin infection, systemic, and peritonitis models [ 18 , 20 , 21 , 25 27 ]. Auranofin is considered safe for systemic administration, with no serious side effects or long-term safety concerns [ 28 ].…”
Section: Introductionmentioning
confidence: 99%